2022
DOI: 10.4103/jfmpc.jfmpc_2406_21
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 lockdown on mental health: A study from rural population of Haryana, India

Abstract: Introduction: COVID-19 (Coronavirus Disease 2019) is a disease caused by a virus named SARS-CoV-2 and was discovered in December 2019 in Wuhan, China, a global threat has largely affected the country’s economic and social values. Moreover, the mitigation strategies being used to counterattack the pandemic attributes a lot of unrest and stress in the masses which has led to several mental health problems like anxiety, depression, sleep loss, post-traumatic stress disorder, etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Similar to previous research on isolation and mental health, it was evident that our participants experienced negative psychosocial effects during this time [38][39][40]. Many of our participants discussed feeling stressed, anxious and depressed each week as a result of social isolation and the unknown of the COVID-19 pandemic [52]. Some participants also indicated somatic complaints, such as back and neck tension [53].…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to previous research on isolation and mental health, it was evident that our participants experienced negative psychosocial effects during this time [38][39][40]. Many of our participants discussed feeling stressed, anxious and depressed each week as a result of social isolation and the unknown of the COVID-19 pandemic [52]. Some participants also indicated somatic complaints, such as back and neck tension [53].…”
Section: Plos Onesupporting
confidence: 82%
“…Fisher and colleagues [51] reported that coping strategies and bereavement behaviors were stunted by the stressors of the pandemic and NPIs. Further, Chhabra and colleagues [52] reported that the practice of socially isolating NPIs leads to increased symptoms of anxiety, depression, stress, post-traumatic stress, and aggression and that these increases could explain the expansion of instances of domestic violence. Sleep quality and duration also diminished as a result of stress or negative emotions caused by living through the social isolation brought on by NPIs [53].…”
Section: Attitudes and Psychosocial Effects Of Npismentioning
confidence: 99%